Using CSR to increase the value of the company - Nováková, Jana; Král, Petr, 1979-; Půbalová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The goal of the thesis is to find if and how active corporate social responsibility can increase the value of company together with identification of the most impactful activities in this regard. For this purpose, the thesis is structured into three parts. The first part provides overview of theoretical approaches to the company value with specific focus on Corporate Social Responsibility, sustainability and communication. In the second part, initiatives in the area of sustainability in a case company are reviewed. For this purpose, a leader and innovator in the area of CSR has been selected with variety of best practices that have been mapped. Based on the conducted research, the third part summarizes recommendations from both theory, as well as practice on those activities that should be considered by other companies for incorporation.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses